High Performance Computing in Science and Engineering ' 06: transactions of the High Performance Computing Center, Stuttgart (HLRS) 2006 - Nagel, Wolfgang E.; Jäger, Willi; Resch, Michael (SpringerLink Bücher, 2007)
Physics -- Gravitational Wave Signals from Simulations of Black Hole Dynamics -- The SuperN-Project: Understanding Core Collapse Supernovae -- MHD Code Optimizations and Jets in Dense Gaseous Halos -- Anomalous Water Optical Absorption: Large-Scale First-Principles Simulations -- The Electronic Structures of Nanosystems: Calculating the Ground States of Sodium Nanoclusters and the Actuation of Carbon Nanotubes -- Object-Oriented SPH-Simulations with Surface Tension -- Simulations of Particle Suspensions at the Institute for Computational Physics -- Solid State Physics -- Nano-Systems in External Fields and Reduced Geometry: Numerical Investigations -- Signal Transport and Finite Bias Conductance in and Through Correlated Nanostructures -- Atomistic Simulations of Dislocation — Crack Interaction -- Monte Carlo Simulations of Strongly Correlated and Frustrated Quantum Systems -- Chemistry -- Characterization of Catalyst Surfaces by STM Image Calculations -- Theoretical Investigation of the Self-Diffusion on Au(100) -- TrpAQP: Computer Simulations to Determine the Selectivity of Aquaporins -- Computational Fluid Dynamics -- Direct Numerical Simulation and Analysis of the Flow Field Around a Swept Laminar Separation Bubble -- Direct Numerical Simulation of Primary Breakup Phenomena in Liquid Sheets -- Direct Numerical Simulation of Mixing and Chemical Reactions in a Round Jet into a Crossflow — a Benchmark -- Numerical Simulation of the Bursting of a Laminar Separation Bubble -- Parallel Large Eddy Simulation with UG -- LES and DNS of Melt Flow and Heat Transfer in Czochralski Crystal Growth -- Efficient Implementation of Nonlinear Deconvolution Methods for Implicit Large-Eddy Simulation -- Large-Eddy Simulation of Tundish Flow -- Large Eddy Simulation of Open-Channel Flow Over Spheres -- Prediction of the Resonance Characteristics of Combustion Chambers on the Basis of Large-Eddy Simulation -- Investigations of Flow and Species Transport in Packed Beds by Lattice Boltzmann Simulations -- Rheological Properties of Binary and Ternary Amphiphilic Fluid Mixtures -- The Effects of Vortex Generator Arrays on Heat Transfer and Flow Field -- Investigation of the Influence of the Inlet Geometry on the Flow in a Swirl Burner -- Numerical Investigation and Simulation of Transition Effects in Hypersonic Intake Flows -- Aeroelastic Simulations of Isolated Rotors Using Weak Fluid-Structure Coupling -- Computational Study of the Aeroelastic Equilibrium Configuration of a Swept Wind Tunnel Wing Model in Subsonic Flow -- Structural Mechanics -- Numerical Prediction of the Residual Stress State after Shot Peening -- Computer-Aided Destruction of Complex Structures by Blasting -- Wave Propagation in Automotive Structures Induced by Impact Events -- Miscellaneous Topics -- Continental Growth and Thermal Convection in the Earth’s Mantle -- Efficient Satellite Based Geopotential Recovery -- Molecular Modeling of Hydrogen Bonding Fluids: Monomethylamine, Dimethylamine, and Water Revised -- The Application of a Black-Box Solver with Error Estimate to Different Systems of PDEs -- Scalable Parallel Suffix Array Construction.